2014
DOI: 10.1155/2014/808247
|View full text |Cite
|
Sign up to set email alerts
|

Individual Genetic Contributions to Genital Shape Variation betweenDrosophila simulansandD. mauritiana

Abstract: External genitalia are one of the most rapidly evolving morphological features in insects. In the Drosophila melanogaster species subgroup, males possess a nonfertilizing external genital structure, called the posterior lobe, which is highly divergent among even closely related species. A previous study on this subgroup mapped two genomic regions that affect lobe size and four that affect lobe shape differences between D. mauritiana and D. sechellia; none of the regions affected both size and shape. Here, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In total, 10 QTLs underlying posterior lobe divergence on the second chromosome was identified (Table S12). This supports the highly polygenic genetic basis of posterior lobe divergence between these species (Liu et al 1996;True et al 1997;Zeng et al 2000;LeVasseur-Viens and Moehring 2014;Tanaka et al 2015). The directions of the effects induced by the introgressed segments were mostly consistent with the interspecific differences, indicating the operation of directional selection on the lobe morphology in these species.…”
Section: Reproductive Isolationsupporting
confidence: 69%
“…In total, 10 QTLs underlying posterior lobe divergence on the second chromosome was identified (Table S12). This supports the highly polygenic genetic basis of posterior lobe divergence between these species (Liu et al 1996;True et al 1997;Zeng et al 2000;LeVasseur-Viens and Moehring 2014;Tanaka et al 2015). The directions of the effects induced by the introgressed segments were mostly consistent with the interspecific differences, indicating the operation of directional selection on the lobe morphology in these species.…”
Section: Reproductive Isolationsupporting
confidence: 69%
“…simulans backcross identified identical QTL as found in a D. mauritiana–D. sechellia backcross ( LeVasseur-Viens and Moehring 2014 ). In the current study, we found three large-effect QTL in the BXD RILs ( Figure 3 ), none of which were found in the LGxSM AIL panel ( Figure S2 ).…”
Section: Discussionmentioning
confidence: 56%
“…It should be emphasized that like the current study, none of these studies have estimated effect sizes from specific genes. Many of these studies were initiated by crossing two closely related species, then backcrossing the F1s to either parental species, including two species of carabid beetles ( Sasabe et al 2007 ), Drosophila simulans and D. mauritiana ( True et al 1997 ; Zeng et al 2000 ; Liu et al 1996 ; LeVasseur-Viens and Moehring 2014 ; Tanaka et al 2015 ), D. simulans and D. sechellia ( Macdonald and Goldstein 1999 ), and D. yakuba and D. santomea ( Peluffo et al 2015 ). Although large-effect QTL were detected in all these studies, the extent of linkage that will exist in these backcross designs, coupled with the limited number of markers used to interrogate the genome, may underestimate the true number of QTL and thus inflate the percent variance explained by any single QTL.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from consideration of linear measurements, a geometric morphometric approach can be applied, and data obtained on size and shape of the trait(s) in focus can be separated and precisely analysed (Zelditch et al, 2004;McPeek et al, 2008McPeek et al, , 2009Gasparini et al, 2011;Cooke and Terhune, 2015). In connection with this, a number of studies are available that link the shape of certain structures (both the "usual morphological" traits and secondary sexual characteristics) with success in mating in the most studied Drosophila species (Menezes et al, 2013;Trajković et al, 2013;LeVasseur-Viens and Moehring, 2014;Richmond, 2014), as well as in other taxa (e.g. Kelly, 2014).…”
Section: Introductionmentioning
confidence: 99%